Application of Assignment and Award Methods to Build Character of Responsibility of Elementary School Students - Trio Erawati Siregar; Rizky Arianty; Irma Sofiasyari; Galuh Mentari Putri (Journal of Elementary Education, 2025)
Character education on responsibility in elementary school students still faces various challenges, particularly in terms of consistency in student behavior in completing learning tasks. This study aims to investigate the implementation of the task and reward method in fostering students’ responsibility character at SDN Mojolangu 3, Malang City while also examining students’ responses as well as the supporting and inhibiting factors affecting its implementation. This study uses a descriptive qualitative approach with subjects consisting of fourth, fifth, and sixth grade students, classroom teachers, the principal, and parents. Data collection techniques include observation, interviews, and questionnaires, which are analyzed through the stages of reduction, presentation, and conclusion drawing with source triangulation. The results showed that the implementation of structured tasks and consistent rewards had a positive impact on improving students' responsible character, as indicated by the positive responses of the majority of students. The main supporting factors included the role of teachers, school support, and parental involvement, while the inhibiting factors included inconsistency in rewards, limited facilities and low intrinsic motivation among some students. This study concludes that the method of assigning tasks and rewards is effective in shaping students' responsible character when applied consistently and contextually.